ANALYSIS OF PUBLIC SAFETY CENTER 119 AMBULANCE SERVICES USING LEAN SIX SIGMA - Thasya Sabilla Putri Rojak; Masyitoh Basabih; Winarto; Roy Michael Suranta (Jurnal Administrasi Kesehatan Indonesia)
Background: DKI Jakarta reports about 5,000 annual deaths from heart disease, disasters, accidents, and other causes. Ambulance demand has risen, especially for COVID-19 cases that require quick medical attention. In 2022, the average emergency response time was 21-30 minutes. Therefore, efforts are needed to improve the response time of PSC 119 ambulances to minimize impacts.